MANAJEMEN SUSU SAPI PERAH DI PETERNAKAN UNIT PELAKSANA TEKNIS DAERAH BALAI PENELITIAN BIBIT PAKAN TERNAK DAN DIAGNOSTIK KEHEWANAN, SLEMAN, DAERAH ISTIMEWA YOGYAKARTA - , RIZKI FEBRIANTO, drh. Untoro, M. S ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This sciencement is result of The Job Training in UPTD BPBPTDK at March 5-9 2013. The purpose of this paper is to complete the requirement of getting the title Diploma Science Veterinary. The result of this paper is the students could apply their studying in campus and cattle breeding to other people and glaziers around Sleman. Moreover to understand of important of drinking the fresh milk and increase peopleâs awareness for growing business of milk cow in this country. Outright the decrease of import milk consumption.The collecting data of this paper are observation method, interview, and compile documentation. The analysis data is giving the meaning into data and make the conlusion from that.Basically management of the cattle breeding in UPTD BPBPTDK is good, but the still have some mistakes. These mistakes are the aspect of productivity and hygienic. For example, in process milking, the milkier do it while smoking. They also never wash their uniform. They also do quality test infrequently. Over this entire situation can decrease the quality of milk in their cattle breeding. This paper suggests to milkier do not smoking when process milking.The quality test of milk be appplied in The Centre of Animal Husbandry UPTD BPBPTDK frequently. It can make consumers feel comfort and health when drinking milk of animal husbandry in UPTD BPBPTDK. The monitoring them into suspect of milk also must be increased.